Clinical systematic review of HuangQi and Shenmai injection plus basic treatment for viral myocarditis in children - Long-Xun Zhu; Jing Jie; Pan-Feng Feng (Elsevier, 2022)
HuangQi (HQ) and Shenmai (SM) are traditional Chinese medicine, which possess a variety of biological activities in the cardiovascular system. We conducted a clinical systematic review of 11 randomized clinical control studies with 1195 participants to evaluate the efficacy and safety of HQ and SM plus basic treatment for viral myocarditis (VM). In the clinical studies, HQ and SM plus basic treatment increased the total effective rates (92.12% vs 75.94%, respectively) and ECG improvement rate (86.67% vs 64.10%, respectively) compared with basic treatment. In addition, the disappearance time of symptoms and signs, myocardial enzymes and ECG recovery time in the study group (HQ and SM plus basic treatment) were significantly shorter than those in basic treatment. The levels of CK, CKMB, LDH, and AST in the study group were significantly lower than those in the control group. Thereby, the combined treatment of HuangQi and Shenmai injection in the treatment of viral myocarditis of children can improve the clinical effect. It is worthy of clinical promotion.